The extract of Cavendish banana (Musa acuminata) peel as antioxidant and anti-aging agents in model yeast Schizosaccharomyces pombe - Theresia Yolanda Avelina; Rika Indri Astuti; Wulan Tri Wahyuni (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Banana peel is one of the wastes that can be explored for various applications. Cavendish is among the most highly consumed bananas in the world, which implies a high amount of banana peel waste. Our study evaluated the potential of Cavendish banana peels as the source of antioxidant and anti-aging agents. Antioxidant was extracted using three different solvents, i.e., water, ethyl acetate, and methanol. Each extract was then assayed for antioxidant activity in vitro using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. The antioxidant and anti-aging activity of the extracts were further evaluated at the cellular level using the yeast Schizosaccharomyces pombe as a model. Our data indicated that the methanol extract of banana peel showed the highest antioxidant activity with an IC50 value of 253.8 µg mL-1 compared to ethyl acetate and water, yet it was considered weak. Interestingly, the methanol extract (600 ppm) showed antioxidant and anti-aging activities at cellular levels in yeast S. pombe. Therefore, this research reveals the potential for developing banana peel methanol extract as a component of pharmaceutical or cosmetic products with antioxidant and anti-aging properties.